Variable temperature micropillar compression to reveal basal slip properties of Zircaloy-4. (15th March 2019) - Wang, Siyang; Giuliani, Finn; Britton, T. Ben
Abstract: Zircaloy-4 is widely used as nuclear fuel cladding materials, where it is important to understand the mechanical properties between room temperature and reactor operating temperatures (around 623 K). To aid in this understanding, we have performed compression tests on micropillars aligned to activate basal slip across this temperature range. Engineering analysis of the results indicates that the plastic yield follows a thermally activated constitutive law. We also observe the nature of the slip bands formed on the side surface of our pillars and see characteristic 'bulging' that tends to localise as temperature increases. Graphical abstract: Unlabelled Image